1970
DOI: 10.1002/tera.1420030110
|View full text |Cite
|
Sign up to set email alerts
|

Cleft palate in A/J mice resulting from restraint and deprivation of food and water

Abstract: A B S T R A C TAiJ mice were subjected to restraint and/or food and water deprivation for 24 or 48 hours beginning on day 14 of' pregnancy. The 48-hour treatment sharply increascd the cleft palate and resorption rates. The data strongly suggest that restraint can cause cleft palate if imposed for an extended period of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

1972
1972
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(14 citation statements)
references
References 6 publications
1
13
0
Order By: Relevance
“…It is noteworthy, however, that fetal mortality markedly increased after stress at the late stages of gestation. This was in agreement with enhanced post-implantation loss following stress for 14 h on GD9 in Swiss mice [11], or for 6-48 h on GD14 in A/J mice [31,32]. Moreover, the body weights of live fetuses in the stress groups were decreased, although there was no statistical significance at the stage of GD5-8.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…It is noteworthy, however, that fetal mortality markedly increased after stress at the late stages of gestation. This was in agreement with enhanced post-implantation loss following stress for 14 h on GD9 in Swiss mice [11], or for 6-48 h on GD14 in A/J mice [31,32]. Moreover, the body weights of live fetuses in the stress groups were decreased, although there was no statistical significance at the stage of GD5-8.…”
Section: Discussionsupporting
confidence: 77%
“…The closure of palatine processes in mice generally occurs on GD 13, and cleft palate is induced by chemicals including dexamethasone and dioxin when they are administered not later than GD13 [23]. It is of interest to compare the failure and occurrence of cleft palate in ICR mice subjected to 12-h restraint for 4 days on GD13 -16 and in A/J mice exposed to 18-48-h stress once on GD14 [31,32], respectively, which may be due to the intensity of stress and strain-difference. Although delayed ossification of vertebral bodies was observed after stress on GD5-8, similar to the observations of Miller and Chernoff [21], abnormalities of sternebrae were enhanced by stress at all of the gestational stages, suggestive of different time schedules in the formation and ossification of skeleton.…”
Section: Discussionmentioning
confidence: 99%
“…This percentage seems to be considerably less than in midpregnancy according to Barlow et al (1,43) and may relate to changing fetal glucocorticoid production and/or the placental mechanisms. Corticosteroids cross the placenta, and stress exposure in d 14 pregnant mice can lead to fetal abnormalities (43,44). The activity of the glucocorticoid-deactivating enzyme 11␤-hydroxysteroid dehydrogenase II, which regulates placental transport of glucocorticoids (45), increases at midpregnancy in the mouse (46) and would limit corticosterone transport, as in the rat (47).…”
Section: Basal and Stress-induced Activity Of The Hpa Axis In Pregnanmentioning
confidence: 99%
“…In mice, deprivation of food and water, which could well be a consequence of severe vomiting, results in a high incidence of embryos with cleft palate (Rosenzweig & Blaustein 1970). Nevertheless, large studies in Finland have shown that there appears to be no association between maternal nausea and vomiting in early pregnancy and subsequent cleft lip or palate in the child (Saxen, 1975a, b).…”
Section: Discussionmentioning
confidence: 99%